The SAARC Paradox: Why South Asia Fails to Integrate - Thapa, Santa Bahadur (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2026)
SAARC is a contradiction in terms for the entire region, with common vulnerabilities but no (real) momentum for unity. This essay explains how vested geopolitical competition and organisational structural inertia have consistently subverted regionalism in the region. Through a digitally-enabled mixed-methods approach, the paper combines quantitative outcome measures of programmes with qualitative thematic analysis of interviews with senior policy-makers. The principal findings are that SAARC is crippled by operational inactivity, largely the result of the India-Pakistan standoff and rigid consensual voting institutions that have forced its members to pursue extraregional alternatives. The paper concludes that SAARC must move to a flexible, multilayered integration model and shift from transactional bilateralism to practical, transformative multilateralism. The paper introduces a novel data-based comparative approach to ASEAN’s successful model. It suggests a new kind of issue-oriented, sector-specific cooperation, in addition to modular ‘economic corridors,’ with which to eventually break out of the region’s entrenched developmental stagnation and institutional paralysis/mistrust.